STRATEGI GURU DALAM MENUMBUHKAN KEPERCAYAAN DIRI SISWA DI SEKOLAH DASAR NEGERI 1 KRAJAN KABUPATEN KLATEN TAHUN PELAJARAN 2022/2023 - pramita sari, ratna; Sri Suwartini; Isna Rahmawati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to find out how the teacher's strategy is in fostering student confidence in Elementary School 1 Krajan, Klaten Regency, for the 2022/2023 academic year. The subjects in this study were 2 class teachers and grade 1 students. The research was conducted at Krajan 1 Public Elementary School, Klaten Regency from May to June 2023. Descriptive qualitative research methodology was used in this study. As opposed to data analysis, which comprises data reduction, data presentation, and conclusions, data gathering employs interviews, observation, and documentation. The results of the study concluded that each teacher has their own stategy to foster student self-confidence at Krajan 1 Public Elementary School, Klaten Regency, students at Krajan 1 Public Elementary School, Klaten Regency on average already have sufficient self-confidence, and there are studens who have confidence low self.